1998
DOI: 10.1007/s004240050541
|View full text |Cite
|
Sign up to set email alerts
|

Q-type Ca 2+ channels are located closer to secretory sites than L-type channels: functional evidence in chromaffin cells

Abstract: This study uses a new strategy to investigate the hypothesis that, of the various Ca2+ channels expressed by a neurosecretory cell, a given channel subtype is coupled more tightly to the exocytotic apparatus than others. The approach is based on the prediction that the degree of inhibition of the secretory response by various Ca2+ channel blockers will differ at low (0.5 mM) and high (5 mM) extracellular Ca2+ concentrations ([Ca2+]o). So, at low [Ca2+]o the K+-evoked catecholamine release from superfused bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…L-type channels predominate the secretion despite their contribution to the total current in single cell experiments is partial or very small, as in the case of BCCs [73,74]. A dominance of L-type channel-mediated secretion is thus reported in bovine [4,[75][76][77], mouse [78,79], rat [9,10,80,81] and cat chromaffin cells [82,83] more or less independently of whether intact adrenal glands or cultured chromaffin cells are used. The reason for this general finding is that during prolonged depolarization (far from physiological conditions) L-type channels are probably more favored because of their slower time-dependent inactivation and lower steady-state inactivation with respect to the other HVA channels (P/Q, N and R), which inactivate more rapidly and completely during prolonged stimuli.…”
Section: L-type Channels and Fast Exocytosis In Chromaffin Cellsmentioning
confidence: 92%
“…L-type channels predominate the secretion despite their contribution to the total current in single cell experiments is partial or very small, as in the case of BCCs [73,74]. A dominance of L-type channel-mediated secretion is thus reported in bovine [4,[75][76][77], mouse [78,79], rat [9,10,80,81] and cat chromaffin cells [82,83] more or less independently of whether intact adrenal glands or cultured chromaffin cells are used. The reason for this general finding is that during prolonged depolarization (far from physiological conditions) L-type channels are probably more favored because of their slower time-dependent inactivation and lower steady-state inactivation with respect to the other HVA channels (P/Q, N and R), which inactivate more rapidly and completely during prolonged stimuli.…”
Section: L-type Channels and Fast Exocytosis In Chromaffin Cellsmentioning
confidence: 92%
“…We (Fig. 2D) and others (7,10) have found that L-type Ca 2ϩ channels, which are known to be loosely associated with release machinery (34,35), mediate somatic exocytosis. In contrast, N-and P/Q types Ca 2ϩ channels, which are closely associated with fusion machinery, are involved in the exocytosis at synaptic terminals (34,36).…”
Section: Discussionmentioning
confidence: 99%
“…2D) and others (7,10) have found that L-type Ca 2ϩ channels, which are known to be loosely associated with release machinery (34,35), mediate somatic exocytosis. In contrast, N-and P/Q types Ca 2ϩ channels, which are closely associated with fusion machinery, are involved in the exocytosis at synaptic terminals (34,36). These observations also are consistent with our conclusion that the intracellular Ca 2ϩ levels required for somatic release is lower than those required for the release from most nerve terminals (4,36).…”
Section: Discussionmentioning
confidence: 99%
“…This slower exocytotic process is primarily controlled by Ca 2+ inXux through multiple isoforms of high-voltage activated Ca 2+ channels, which contribute to secretion proportionally to their density of expression and gating properties, with no speciWc requirements of Ca 2+ channels colocalization to the release sites (Kim et al 1995;Engisch and Nowycky 1996;Klingauf and Neher 1997;Lukyanetz and Neher 1999;Ulate et al 2000;Carabelli et al 2003;Chan et al 2005;Giancippoli et al 2006;Polo-Parada et al 2006). Alternatively, other groups suggest a preferential role of some channel subtype in close proximity to the secretory sites (Lopez et al 1994;Artalejo et al 1994;Lara et al 1998;O'Farrel and Marley 2000;Albillos et al 2000) and a further role of mitochondria in sequestering Ca 2+ entering through Ca 2+ channels (Ales et al 2005). In addition to this, the eYciency of stimulus-secretion coupling can be altered in many ways, some relevant examples are: (1) PKC activation, which enhances exocytosis (Gillis et al 1996), (2) rapid and sustained increase of intracellular cAMP, which potentiates Ltype channel densities and secretion at diVerent proportions , (3) transdiVerentiation of chromaYn cells with astrocyte-conditioned medium, which promotes the acquisition of a neuronal phenotype and accelerates the exocytotic kinetics, by a better coupling between secretory vesicles and Ca 2+ channels (Ardiles et al 2006) and (4) -adrenergic stimulation, which enhances the stimulus-secretion coupling of Ltype Ca 2+ channels by repeated action potential-like stimulations (Polo-Parada et al 2006).…”
Section: Introductionmentioning
confidence: 99%